Wilkie’s Syndrome following Chemotherapy: A Case Report and a Review of Literature - Nicholas J. Corsi; Ahmad A. Abu-Heija; Anand Kumar Ravi; Matthew P. Corsi; Murray N. Ehrinpreis (Case Reports in Gastrointestinal Medicine)
Superior mesenteric artery (SMA) syndrome is a rare etiology of upper gastrointestinal obstruction. The measured angle between the SMA and the aorta is typically between 38 and 65° and maintained by mesenteric fat. Excessive fat loss can lead to intestinal obstruction due to an exaggerated acute angularity of the SMA, compressing the third part of the duodenum. We present a 22-year-old female with a history of aplastic anemia, status post bone-marrow transplant, who presented with intractable nausea and had confirmed SMA syndrome on CT angiography. Subsequently, the patient underwent nasogastric decompression and successful laparoscopic duodenojejunostomy.